An exploratory study of beliefs and understandings of health workers at Onandjokwe hospital, Namibia regarding child sexual abuse - Meguid, Tarek (Department of Paediatrics and Child Health, 2024)
The study presented here examines beliefs and understandings of health workers at Onandjokwe Lutheran Hospital, regarding sexual abuse of children. The introduction gives background information on the area where Onandjokwe Hospital is situated and on the magnitude of the problem of sexual abuse of children here. It also provides information on what is known about beliefs and attitudes of health workers and on facts of CSA. The literature review gives an overview of the literature on child sexual abuse. In this section an attempt is made to also look at the history of research in this area and at the specific problems of studying such a sensitive issue in cultural settings different from the setting of the researcher. This review includes literature on medical, social, anthropological, legal, cultural and political aspects of CSA. As much literature dealing with this subject in the African, Southern African and Namibian context as possible is included in this review. The chapter on methodology explains the study design and its biphasic approach combining a qualitative and a quantitative phase. The qualitative phase consists of several focus group discussions leading to the fonnulation of questions for the questionnaire used during the quantitative phase of the study. Problems and limitations are also discussed. The findings of the study are presented in two parts, one part for each of the two phases. The qualitative findings are based on three focus group discussions held with various categories of health workers. The quantitative findings are based on 186 questionnaires. They are shown mainly in tables and graphs. At the end of the chapter results are further analysed looking at specific sub-sets of respondents. Since analysis of the collected data could be very extensive and take many forms, a decision was taken to present descriptive exploratory data for the purposes of this dissertation. All answers to the main part of the questionnaire are shown in table 26 which is provided as an appendix so as to allow for further analysis if one may wish to do so. In the discussion the overall findings emerging from this study are discussed first, followed by specific aspects of the analysis. The main results of the study are that CSA is perceived to be a significant problem in the study area and that health workers do not feel competent enough to handle this problem. They clearly express the need to be trained further in this field. Although the overwhelming majority of medical doctors are from abroad and a number of other health workers have been raised abroad; the majority of health VII workers are Namibian, are nurses and have been raised in the area of the country in which the study was undertaken. The beliefs and understandings of CSA found in this study therefore reflect mainly 'local' views. The discussion then leads to the formulation of brief conclusions and recommendations. An extensive bibliography, including all the available literature on CSA in Namibia to date, and the appendices, consisting of the Ndonga and English questionnaire and a foldout list of acronyms for convenience conclude this thesis.